Laser pulse energy detector. - Campos, JSD (1997)
This work describes the construction of a pyroelectric detector for measurements of laser pulse energy, using the polymer Polyvinylidene Fluorid (PVDF). The experimental data measured by detector showed a linear response for energy between 0,4 to 6,8 mJ/pulse for 8,3 milisecond duration pulse.